Osteochondroplasty and Labral Repair for the Treatment of Young Adults With Femoroacetabular Impingement: A Randomized Controlled Trial. Issue 1 (January 2021) - ,; Ayeni, Olufemi R.; Karlsson, Jon; Heels-Ansdell, Diane; Thabane, Lehana; Musahl, Volker; Simunovic, Nicole; Duong, Andrew; Bhandari, Mohit; Bedi, Asheesh; Järvinen, Teppo; Naudie, Douglas; et al.
Background: Femoroacetabular impingement (FAI) is a condition known to cause hip pain in young adults. Purpose: To evaluate the efficacy of the surgical correction of FAI via arthroscopic osteochondroplasty with or without labral repair compared with arthroscopic lavage of the hip joint with or without labral repair. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 220 male and female participants aged 18 to 50 years with nonarthritic FAI suitable for surgical treatment were recruited for the trial at 10 clinical centers in Canada, Finland, and Denmark between October 2012 and November 2017, of whom 214 were included in the final analysis. In the osteochondroplasty group, cam- and/or pincer-type lesions were resected using fluoroscopic guidance. In the lavage group, the joint was washed out with 3 L of normal saline. Surgeons were instructed to repair the labrum in both groups if it was mechanically unstable once probed, showing visible displacement or chondrolabral separation. The primary outcome was patient-reported pain (using the 100-point visual analog scale [VAS]) at 12 months. Secondary outcomes included hip function (Hip Outcome Score [HOS] and International Hip Outcome Tool), physical and mental health (12-Item Short Form Health Survey), and health utility (EuroQol–5 Dimensions) at 12 months as well as any reoperations and other hip-related adverse events at 24 months. Results: At 12 months, there was no difference in pain (VAS) between the groups (mean difference [MD], 0.11 [95% CI, –7.22 to 7.45]; P = .98). Also, 88.3% (189/214) of participants had a labral tear, of which 60.3% were repaired. For the secondary outcomes, there were no significant differences between treatment groups, with the exception of the HOS activities of daily living domain in which lavage showed significant improvement compared with osteochondroplasty (MD, –5.03 [95% CI, −10.40 to −0.03]; P = .049). By 24 months, there were significantly fewer reoperations reported in the osteochondroplasty group (8/105) than the lavage group (19/104) (odds ratio, 0.37 [95% CI, 0.15-0.89]; P = .026). The primary reasons for a reoperation included hip pain (15/27; 55.6%) and a reinjury of the labrum (11/27; 40.7%). Conclusion: Both the osteochondroplasty and the lavage groups with or without labral repair for FAI had significantly improved pain or function significantly at 1 year. By 2 years, the reoperation rate was significantly lower in the osteochondroplasty group. Registration: NCT01623843 (ClinicalTrials.gov identifier)